Efeitos do esporte sobre o comportamento pró-social atribuídos a participantes de um projeto social - Rosa, Diogo Mello (2016)
Brazilian society has experienced significant economic development in the past 20 years, as a result, the country has undergone important changes in its socioeconomic structure. In this context, a number of policies have been implemented in Brazil in order to improve social and economic conditions of the most marginalized sections of the population. Amid a variety of sources, structural characteristics and objectives, many of these actions adopt the sport (understood here in a broad sense) as content or means to educate children and young people, based on the belief of their potential to influence and / or promoting values, attitudes and behaviors, or even to promote social inclusion. Thus, this study aimed to understand the effects of social projects that use sport, giving priority to research on the effects of her experience in the prosocial behavior of its participants, as research locus design Knowledge Sierra Station, with novice users track and field, soccer, swimming and sports initiation. The purpose of this research has required the need to mobilize, methodologically a quantitative and qualitative study of pre-test type / post-test design with "quasi-experimental" with nonrandomized groups (Kerlinger, 1986). For the evaluation of prosocial behavior use the Prosocial Behaviour Questionnaire - PBQ (WEIR; Duveen, 1981). The difference between the mean pre- and post-tests, was obtained by technical McNemar and Kappa. The reliability of the instrument application was measured by Alpha calculation Crombach, being 0892 to 0942 pretest and post-test, achieving a high degree of reliability. The results indicate that the student profile is predominantly male, approximately 62% of the project participants, and between the ages of 6 to 17 years with a mean age of 10.23 years students, especially the younger students in the study, with about 60% of the participants have less or even 10 years. We can extract only the question 17 of the questionnaire participants did not show a statistically significant change, generating results in 95% of the issues in question, showing by empirical data that there is a positive relation to the existence of pro-social behavior as a result of sports. Finally, in conclusion, it is suggested that scientific production in the area mobilizes its efforts to analyze in greater depth the content related to prosocial behavior and the influence of sport in social projects.